2016
DOI: 10.31018/jans.v8i3.987
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cropping systems on soil properties, nutrient availability and their carbon sequestration potential in Shiwalik hills of Himachal Pradesh

Abstract: The impact of cropping systems on soil properties, nutrient availability and their carbon sequestration potential was studied during the years 2014 and 2015 in Shiwalik hills of Himachal Pradesh. The four commonly occurring cropping systems namely vegetable, fruit, cereal crop and agroforestry were selected. Uncultivated land in the region was considered as control. In total, there were five treatments which were replicated six times under randomized block design. The study indicated that the cropping systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…A significant lower pH was observed in monocropping and highest pH was observed in Cauliflower-Maize rotation [9]. Similarly Loria, et al [10] revealed that higher soil carbon, soil nitrogen, phosphorus and potassium were observed in vegetable cultivation compared to cereals.…”
Section: Introductionmentioning
confidence: 90%
“…A significant lower pH was observed in monocropping and highest pH was observed in Cauliflower-Maize rotation [9]. Similarly Loria, et al [10] revealed that higher soil carbon, soil nitrogen, phosphorus and potassium were observed in vegetable cultivation compared to cereals.…”
Section: Introductionmentioning
confidence: 90%
“…The elevated levels of P avail , Na and Ca concentrations in HG may be attributable to the application of animal and household waste like dung and ash since these amendments are an important source of Ca, P, K and other nutrients (Voundi Nkana, 1998; Ovung et al, 2021). In addition, incorporation of conservation tillage, manure application and adoption of integrated agroforestry-based cropping systems are vital in minimizing adverse impacts on soil quality and efficient use of nutrients (Loria et al, 2016). In comparison to the other land use systems, the lower values of exchangeable Na, Mg, K, Ca and Mn in cultivated soils of AP and CJ may also be attributed to the nutrient uptake by plants for their growth and development.…”
Section: Effect Of Land Use and Soil Depths On Exchangeable Cations (Na Mg K Ca And Mn)mentioning
confidence: 99%
“…Whereas the studies of Ogunkunle 2013;Yahaya et al, 2014;Hacimuftuoglu & Oztaz, 2017;Suleiman, et al, 2017;Rajesh et al, 2017;Oriola & Atiyong, 2020 found differences in the properties of soils under different cropping systems. Whereas, Loria et al, 2016 found that the traditional cropping systems had no influence on the soil properties. Given that soil fertility management is fundamentally important to achieving sustainable agricultural production (Abdulwahab et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…These changes directly affect the composition, properties and productivities of the soil (Oriola and Hammed, 2012). In some cases, spatio temporal variations in soil properties depict changes in geology (Burke, 2002;Koojman et al, 2005;Umeri et al, 2017); climatic change (Dexter & Richard, 2009) and soil management practices (Amusan et al, 2006;Basaran et al, 2006;Gupta et al, 2009;Yakub, 2012;Ogunkunle, 2013;Loria et al, 2016). The physico -chemical properties (pH, soil texture, moisture, porosity, bulk density, soil organic carbon, organic matter, cation exchange capacity, total nitrogen, phosphorus and potassium) of soil affect nutrients' availability, biota growing conditions, and soil physico -chemical and biological properties (Yakub, 2012).…”
Section: Introductionmentioning
confidence: 99%